2016
DOI: 10.1152/ajpgi.00363.2015
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor-κB regulates the expression of multiple genes encoding liver transport proteins

Abstract: Balasubramaniyan N, Ananthanarayanan M, Suchy FJ. Nuclear factor-B regulates the expression of multiple genes encoding liver transport proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Most importantly, it was demonstrated that pretreatment with FXR agonists (GW4064 and 6ECDCA) suppressed NF-κB agonist-induced inflammatory gene expression in an FXR-dependent manner in HepG2 cells and mouse primary hepatocytes [30]. NF-κB binding sites were identified on FXR and FXR target genes BSEP , SHP , MRP2 , MDR3 , and ABCG5/G8 ; specifically, NF-κB bound to the promoter of BSEP and actively suppressed transcription [37]. Overexpression of NF-κB recruited nuclear receptor co-repressor 2 (SMRT), and blocked FXR binding to its FXRE [37].…”
Section: Adaptive Immune Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly, it was demonstrated that pretreatment with FXR agonists (GW4064 and 6ECDCA) suppressed NF-κB agonist-induced inflammatory gene expression in an FXR-dependent manner in HepG2 cells and mouse primary hepatocytes [30]. NF-κB binding sites were identified on FXR and FXR target genes BSEP , SHP , MRP2 , MDR3 , and ABCG5/G8 ; specifically, NF-κB bound to the promoter of BSEP and actively suppressed transcription [37]. Overexpression of NF-κB recruited nuclear receptor co-repressor 2 (SMRT), and blocked FXR binding to its FXRE [37].…”
Section: Adaptive Immune Responsementioning
confidence: 99%
“…NF-κB binding sites were identified on FXR and FXR target genes BSEP , SHP , MRP2 , MDR3 , and ABCG5/G8 ; specifically, NF-κB bound to the promoter of BSEP and actively suppressed transcription [37]. Overexpression of NF-κB recruited nuclear receptor co-repressor 2 (SMRT), and blocked FXR binding to its FXRE [37]. Direct interaction between FXR and NF-κB was further confirmed in vivo , NF-κB recruitment to FXR and BSEP promoter was increased in models of disease and inflammation (bile-duct ligation and LPS-injection) [37], confirming previous observations of suppressed FXR signaling during inflammatory response [30, 38].…”
Section: Adaptive Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that mixed lineage leukemia 3, a histone H3 lysine 4 lysine methyltransferase, is depressed after CBDL in mice, and this epigenetic mark is essential to activation of Abcc2 by the nuclear receptor FXR . We have also reported that transcription factor nuclear factor kappa B (NF‐κB) suppresses the transactivation of ABCC2 by FXR in vitro , and that NF‐κB activation in the context of obstructive cholestasis in mice establishes a repressive chromatin environment at the promoters of several FXR‐target genes, including the promoter of Abcc 2 through recruitment of HDACs and corepressors . It is likely that these and other mediators act in concert with let7a‐5p to repress ABCC2 expression in cholestasis, but the relative importance of each pathway during the progression of liver disease has not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…Following protein transfer, the blots were blocked with 5% Nonfat Dry Blot Omniblok (American BioAnalytical, Natick, MA) in 1 × blocking buffer (diluted from 10 × Tris‐buffered saline with 0.5% Tween 20 [Kirkegaard & Perry Lab Inc., Gaithersburg, MD]). Following blocking, incubation with primary antibodies (to BSEP, MRP2, NTCP, FXR, and β‐actin) with secondary peroxidase‐conjugated antibodies and the washing steps was done as previously described . Signals developed with Clarity western ECL substrate (Bio‐Rad) were quantitated using the Bio‐Rad ChemiDoc System.…”
Section: Methodsmentioning
confidence: 99%